Ten years of Urban Forestry & Urban Greening - The stories behind the articles (2011)
This issue concludes the 10th volume and year of Urban Forestry & Urban Greening. During these exciting first ten years of the journal, we have published a wide range of scientific articles, dealing with many aspects of urban green spaces and their planning, design and management. Presented research has looked at anything from the relations between nature and stress to tree pruning. When articles are published, one tends to forget to hard work needed to get to the stage of a final publication. Sometimes several years of research and writing are needed to get to the publication stage. Writing scientific articles is often demanding. Moreover, there are interesting stories behind these articles, stories that seldom become known. To celebrate ten years of Urban Forestry & Urban Greening, we asked the authors of five articles to briefly write up the stories of how their articles came into being. These stories give a more human face to scientific publishing and show that, apart from good science and hard work, publishing can also be the result of unexpected events or sudden inspiration.